EU Trade Preferences and Export Diversification - Maria Persson; Fredrik Wilhelmsson (Lund University, School of Economics and Management, Department of Economics, 2013)
Since at least the 1960s, the European Union (EU) has offered various kinds of non-reciprocal trade preferences for developing countries. Originally, these trade preferences had at least two policy goals: (i) to increase export volumes for developing countries and thereby boost their export earnings, and (ii) to facilitate export diversification. While extensive research has confirmed that the first of these goals is typically met, the second goal seems to have been largely forgotten by researchers as well as in policy circles. The aim of this paper is therefore to analyse the impact of the EU's non-reciprocal trade preferences for developing countries on export diversification. Our estimation results suggest that some trade preference programs, such as the Generalised Scheme of Preferences (GSP), are associated with increasing ranges of export products. By contrast, preferences offered to Mediterranean countries typically have no significant effects, and African, Caribbean and Pacific (ACP) preferences actually have negative effects toward the end of our time period, suggesting that ACP countries may respond to preferences by specializing into fewer goods.
Keywords: F13; F15; O24; 330; Export diversification; non-reciprocal trade preferences; GSP; ACP; EU